Aproximación al estado de la educación artística en las ciudades de Machala y Pasaje, Ecuador - Espinoza Freire, Enrique (2018)
The world and especially Latin American, about arts education conferences has been an attempt to influence the problem of teaching. One of the initiator of this series of debates, projects and program management education around this appear to be linked to the one held in Bogota from 28 to 30 November 2005, under the slogan "Towards Quality Education: Challenges and Opportunities ". The Conference brought together 21 countries, and the Academic Committee of the event sent the concept paper prepared by the Regional Office for Culture of UNESCO and a questionnaire to be filled jointly by the delegates of education and culture. That questionnaire was a methodological pretext for a local look at this issue, because the pronouncements of the "Declaration of Bogota", are still in force in our country. Besides inspiring and constitute the foundations of the Educational Goals 2021. This survey provides a reflection on the scope, which necessarily precedes a more comprehensive introduction, the art education program in the appropriate institutional framework. What is significant is that the identification of opportunities and challenges, including the characterization of the imaginary in place that hinder or enhance its more or less successful establishment, so, adapting the Ecuadorian context, a characterization is aimed at practicing teachers in the Basic Education educational institutions of the city of Pasaje and Machala in Ecuador.